The Characteristics of Instant Bose Corn Processed with Various Cooking Methods - Lista Eka Yulianti (Perum BULOG, 2022)
Bose corn is an ethnic food from East Nusa Tenggara, made from corn and beans. The process ofmaking bose corn takes a long time, which is about 4 hours. Instantization can shorten the preparationtime of bose corn until it is ready to eat. The cooking process is one of the stages in the instantization.This study aimed to determine the appropriate cooking method for the bose corn instantization and toassess its effect on the instant bose corn characteristics. This research was carried out using the combinedcooking method (mixed and boiled-steamed, and mixed boiled-autoclaved, mixed and steamed-autoclaved,unmixed and boiled-steamed, unmixed and boiled-autoclaved, and unmixed and steamed-autoclaved). Theresults showed that various cooking methods significantly affected the instant bose corn’s physical andchemical attributes. Compared to other methods, the mixed and boiled-autoclaved method produced thebest characteristics of instant bose corn. This instant bose corn had 6.38 minutes of rehydration time, 0.29g/ml of bulk density, 190.00 percent of volume expansion, 262.55 N of hardness, 7.44 percent of moisture,13.84 percent of protein, and 1.55 mg/100g of iron content.